1993
DOI: 10.1061/(asce)0733-950x(1993)119:2(123)
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Fine Sands by Currents and Waves

Abstract: ABSTRACT:The transport process of fine sands in combined current and wave conditions in a flume was studied. Two types of sediment material were used, a very fine sand with a median diameter of about 100 ~m and a medium-fine sand with a diameter of 200 txm. The current velocities were varied in the range of 0.1-0.5 m/s (following and opposing the waves). Irregular waves with a single-topped spectrum and peak period of 2.5 s were generated. The significant wave height varied in the range of 0.075 m to 0.18 m. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 15 publications
(14 reference statements)
1
36
0
Order By: Relevance
“…Complete overviews of the formulations, testing, and validation of Delft3D Online Morphology have been reported in Lesser et al (2004). See Walstra and Van Rijn (2003), and Van Rijn (1993, 2007a for the specific transport formulations. Because most fringing reefs are relatively uniform alongshore in water depth and hydrodynamic roughness at larger scales (order *100 s of m) but heterogeneous at smaller scales (order *m) due to ridge-and-runnel structures on the reef flat and spur-and-groove structures on the fore reef, a fully realistic three-dimensional model at the spatial scales necessary to resolve the heterogeneity would be too computationally intensive.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Complete overviews of the formulations, testing, and validation of Delft3D Online Morphology have been reported in Lesser et al (2004). See Walstra and Van Rijn (2003), and Van Rijn (1993, 2007a for the specific transport formulations. Because most fringing reefs are relatively uniform alongshore in water depth and hydrodynamic roughness at larger scales (order *100 s of m) but heterogeneous at smaller scales (order *m) due to ridge-and-runnel structures on the reef flat and spur-and-groove structures on the fore reef, a fully realistic three-dimensional model at the spatial scales necessary to resolve the heterogeneity would be too computationally intensive.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Figure 5-14 shows verification of some experimental cases of Zhou and Ju (2007), Havinga (1992) and van Rijn et al (1993) with low ripple steepness and Table 5-2 shows the experimental conditions. It can be seen that the calculated sediment concentration profiles fit the measured data reasonably.…”
Section: Verificationmentioning
confidence: 82%
“…As this kind of bed type is a transition zone between vortex ripples and sheet flow, the turbulence diffusion is very complex and still needs further study. Zhou and Ju (2007), Havinga (1992) and van Rijn et al (1993) …”
Section: Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to calibrate the high concentration layer near seabed, the sediment concentration profiles due to combined waves and current for multi-sized sediment simulated by the modified model are compared with the experimental values by van Rijn, et al (1993), and the results are shown in Fig. 3.…”
Section: Verificationmentioning
confidence: 99%